A Lateral Reading of Religion: Christianity in Sister Relationships - Sharma, Sonya (Journal of contemporary religion, 2016)
Sociologists of religion continue to give precedence to parent-child transmission in studies on religion and family. In doing so, other kinds of family relationships that also influence religious beliefs and practices remain in the background. In this article, instead of using a vertical lens, religion in the family is approached through a lateral reading of sisters' religious lives. Drawing on 13 biographical accounts, which included family diagrams and time-lines, conducted with adult women who identified as sisters and as Christian, this article examines the intersection of religion with practices of intimacy and social context. By looking laterally, this article explores the mutual shaping of religion and sibling ties and gives recommendations for the way this under-researched area can expand the sociological study of religion within families.